Burned peatlands within the Volyn region: state, dynamics, threats, ways of further use - Fesyuk, Vasyl O.; Moroz, Iryna A.; Chyzhevska, Larysa T.; Karpiuk, Zoia K.; Polianskyi, Serhii V. (Geological - Geographical Faculty of the Oles Honchar Dnipro National University, 2020)
The consequences of peat fires are complete or partial loss of soil fertility over a considerable area of land, decrease in biodiversity, razing of unique landscapes, deterioration of the conditions for life and health of the population, disturbed carbon cycle, increase in the greenhouse gas emissions, intensification of climate change, etc. Climatic tendencies of recent years will further contribute to increase in peat fires and their negative aftermaths. Therefore, prevention of peat fires and recultivation of burned-out peatlands are extremely important nature-protective measures. The objectives of the article was evaluation of current condition of burned peatlands of Volyn Oblast, their territorial distribution, dynamics according to years, analysis of potential threats for ecological safety and development of recommendations for prevention of peat fires and overcoming the negative consequences. During the study we used: methods of collecting material, methods of statistical analysis of results, cartographic methods, methods of expert assessment. We determined that the problem of peat fires and burned peatlands is extremely relevant for Volyn Oblast, requiring development of a complex of measures to solve it. As of 2002, the area of burned peatlands in the Oblast accounted for 440 ha. For the period of 2002-14, a total of 803 ha of burned peatlands was recorded across Volyn Oblast. In 2015-19, their area increased by another 280 ha. The largest areas of burned peatlands were found in Kamin-Kashyrskyi (137.9 ha), Liubeshiv (26.72 ha), Manevychi (20.35 ha) districts. We determined the tendency towards increase in the number of fires and areas of burned peatlands starting from 2018. To prevent peat fires, two-sided (wetting and drying) regulation of water regime within reclamation systems, alkalinization of peat soils, increase in their fertility, sanding-up of dried peat soils are proposed. Also, important measures include monitoring of burned peatlands and prevention of wildfires. In order to further use, rehabilitate and recultivate burned peatlands, it is suggested to t inventorise burned peatlands, assess economic and ecological damages, develop a plan of further use of territories, determine priorities of development and propose corresponding economic and nature-protection measures.
Keywords: burned peatlands; peat fires; consequences of peat fires; dynamics of peat fires; measure to reduce negative effects of peat fires; recultivation of burned peatlands